MOTIVATION WHICH AFFECTS DECISION-MAKING ON ROOFTOP SOLAR POWER SYSTEM INSTALLATION BY RESIDENTS IN MUEANG DISTRICT, RAYONG PROVINCE - NONG HTAIK, PHU; Phongpaew, Aniruth; Vikraipat, Tawan; Loppananusorn, Songpol (Journal of MCU Phetchaburi Review, 2026)
The study on decision-making regarding rooftop solar power system installation by residents in Mueang District, Rayong Province aimed to examine the demographic characteristics of residents in relation to motivations affecting their decision to install rooftop solar power systems, and to study the motivations influencing these installation decisions. The sample group consisted of household representatives who owned houses, buildings, or structures in Mueang District, Rayong Province. The researcher determined the sample size of 400 people. Purposive sampling was used, with questionnaires as the data collection tool. Statistics used for data analysis included percentage, mean, standard deviation, t-test, one-way ANOVA. Results of the study found that:1. Different demographic characteristics in terms of gender, age, education, occupation and average monthly income result in varying decisions regarding the installation of rooftop solar power systems 2. security and safety, competition or imitation, durability, and financial aspects were found to have relationships with and influence on residents' decisions to install rooftop solar power systems